BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU MTs SEKECAMATAN WINONG KABUPATEN PATI - Sahlan, 12.5202.0257; Sutomo, Y (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of intrinsic motivation and emotional intelligenceon the performance of teachers in MTs Sekecamatan Winong moderated Pati regency withorganizational culture. The specific objectives of this study was to examine the effect ofintrinsic motivation and emotional intelligence on the performance of teachers who aremoderated by the role of organizational culture. The usefulness of this study is to clarifyand extend previous research on the effect of intrinsic motivation and emotionalintelligence on the performance of teachers who moderated the organizational culture.This study used a population of teachers in MTs Sekecamatan Winong Patiregency much as 173 teachers. Sampling techniques in this study is non probabiltysampling with purposive sampling method. The method used in this research is multipleregression with interaction quasi moderation.Based on the results of the study can be summarized as follows intrinsicmotivation does not affect the performance of teachers, emotional intelligence does notaffect the performance of the teacher, organizational culture does not affect theperformance of the teacher, the influence of intrinsic motivation on teacher performance ismoderated by organizational culture, and there is the influence of emotional intelligenceon performance teachers are moderated by organizational culture.Keywords: emotional intelligence, organizational culture, intrinsic motivation, Performance teacher.